Emerging Pollutants Some Strategies for the Quality Preservation of Our Environment - Soloneski, Sonia; Larramendy, Marcelo L. (IntechOpen, 2018)
This edited book, Emerging Pollutants - Some Strategies for the Quality Preservation of Our Environment, contains a series of chapters providing some strategies for the preservation of our environmental quality focusing on the different categories of environmental pollutants and their negative consequences on living organisms.